Cathepsin K in lymphangioleiomyomatosis: LAM cell-fibroblast Interactions enhance protease activity by extracellular acidification - Dongre, Arundhati; Clements, Debbie; Fisher, Andrew J.; Johnson, Simon R. (Elsevier, 2017)
Lymphangioleiomyomatosis (LAM) is a rare disease in which clonal ‘LAM’ cells infiltrate the lungs and lymphatics. In association with recruited fibroblasts, LAM cells form nodules adjacent to lung cysts. It is assumed LAM nodule derived proteases lead to cyst formation although, this is uncertain. We profiled protease gene expression in whole lung tissue and observed cathepsin K was 40 fold over-expressed in LAM compared with control lungs (p≤0.0001). Immunohistochemistry confirmed cathepsin K protein in LAM nodules but not control lungs. Cathepsin K gene expression, protein and protease activity was detected in LAM associated fibroblasts but not the LAM cell line 621-101. In lung nodules, cathepsin K immune reactivity was predominantly co-localised with LAM associated fibroblasts. In vitro, extra-cellular cathepsin K activity was minimal at pH 7.5 but significantly enhanced in fibroblast cultures at pH 7 and 6. 621-101 cells reduced extracellular pH by 0.5 units over 24 hours. Acidification was dependent upon 621-101 cell mTOR activity and net hydrogen ion transporters, particularly sodium/bicarbonate co-transporters and carbonic anhydrases which were also expressed in LAM lung tissue. In LAM cell/fibroblast co-cultures, acidification paralleled cathepsin K activity and both were inhibited by sodium bicarbonate co-transporter (p≤0.0001) and carbonic anhydrase inhibitors (p=0.0021). Our findings suggest cathepsin K activity is dependent on LAM cell/fibroblast interactions and inhibitors of extracellular acidification may be potential therapies for LAM.